Investigation of the Integrity of aC:H Coatings on Stainless Steel Micro-Moulds during Thermal Cycling - Griffiths, C.A.; Rees, A.; Llewelyn, G.; Fonseca, O. V. (Journal of Coating Science and Technology, 2018)
Micro-injection moulding (µIM) is a key technology for scaling down larger geometry components and can include functional features at the micrometre scale and as far as the sub-micrometre length scale. Thermal cycling of amorphous hydrogenated carbon (aC:H) coated Stainless Steel (SS) has been investigated to simulate long-term micro-injection moulding (µIM) wearing and damage. Micro indentations and cracks were made into the mould and predictions of the crack behaviour were made using thermal expansion models. Validation of the results was performed with multiple heating and cooling cycles along with hardness measurements of the damage to the coating. The undamaged surfaces showed no major deformation but the cracks were shown to propagate and change in behaviour. The first two heat cycles of the testing had the most significant effect on the substrate with varying thermal expansions of materials being the main cause. The aC:H is shown to have excellent properties for mould tool applications but delamination could occur in areas susceptible to damaged and periodic surface inspection will be required preserve tool life.